Active metabolite concentration of clopidogrel in patients taking different doses of aspirin: results of the interaction trial. (4th February 2015) - Liang, Y.; Hirsh, J.; Weitz, J. I.; Sloane, D.; Gao, P.; Pare, G.; Zhu, J.; Eikelboom, J. W.
Summary Background The CURRENT‐OASIS‐7 and PLATO trials suggest that the benefit of clopidogrel is influenced by the dose of aspirin. Objective To explore a potential pharmacokinetic interaction between aspirin and clopidogrel, and determinants of clopidogrel active metabolite (AM) levels. Methods In part 1, using a 2 × 2 factorial design, we randomized patients to clopidogrel 600 mg loading dose (LD) followed by 150 mg day−1 for 6 days and 75 mg day−1 thereafter, or clopidogrel 300 mg LD followed by 75 mg day−1 thereafter, and compared aspirin at 325 mg or 81 mg day−1. In part 2, patients were given a 600‐mg clopidogrel LD, and were randomly allocated to aspirin 325 mg or 81 mg day−1. We combine the data from the two parts. Blood samples were collected 1 h after administration of the study drug. Results We randomized 302 patients (mean age 60.4 ± 9.9 years). Clopidogrel AM levels were similar in patients randomized to aspirin 325 or 81 mg (geometric mean, 12.70 ng mL−1; 95% CI, 10.96–14.72 ng mL−1; and geometric mean, 12.55 ng mL−1; 95% CI, 10.80–14.58 ng mL−1; P = 0.91). Blood levels of clopidogrel were lower in CYP2C19*2 loss‐of‐function (LOF) carriers compared with non‐carriers (10.72 ng mL−1; 95% CI, 8.83–13.01 ng mL−1; and 15.21 ng mL−1; 95% CI, 13.30–17.40 ng mL−1, respectively; P = 0.003) whereas levels in gain of function carriers and non‐carriers were similar (13.31 ng mL−1; 95% CI, 11.53–15.35 ng mL−1; and 14.07 ng mL−1; 95% CI, 11.74–16.87 ng mL−1, respectively; P = 0.4). Independent baseline predictors of clopidogrel AM levels were LOF genotype, body mass index, diabetes, proton pump inhibitor use and creatinine clearance, but accounted for only 20% of the variability in levels. Conclusion Aspirin dose does not predict clopidogrel AM levels 1 h post‐LD. Most of the variability in clopidogrel AM levels is not explained by patient characteristics or CYP2C19 metabolizer status.